TAFSIR FI SABILILLAH DAN IMPLIKASINYA BAGI CAKUPAN FI SABILILLAH SEBAGAI MUSTAHIK ZAKAT - Muhammad Sarbini (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2018)
ABSTRACTThis paper proposes the reinterpretation of the characteristics of the recipient of zakát fī sabīlillāh, between a narrow meaning only for volunteer soldiers who fought in battle and the broad meaning that includes all those who observe obedience. The subject of the recipient of zakát fī sabīlillāh has been concentrated on the scope of meaning fī sabīlillāh in language and specifically to the word fī sabīlillāh as an expression of the meaning of jihád and war. The meaning of fī sabīlillāh in the Qur'an and tradition which is primarily meant as the meaning of warfare is felt to be irrelevant to the existence of other references explaining the meaning of sabīlillāh or jihád for pilgrimage or study, and irrelevant by time. On the other hand, expanding the meaning of sabīlillāh to all those who observe obedience is also considered inaccurate with the purpose and function of zakát described by the texts of revelation. Therefore, the reinterpretation of the meaning of fi sabīlillāh as jihád as desired by the revelation itself and on the other hand by the decision of the majority of fiqh scholars mentioned previously, should the sabilillah's evolving meaning remain focused on the meaning of jihád , the purpose of jihád and the particular characteristics of jihád. Thus, it is found that the two main sides of zakát legal construction given to the recipient of zakát Fī sabīlillāh are extensions of meaning based on the basic characteristics of the zakát meaning, the main purpose, and the function of the zakát itself which is centered on the state's finances in managing the basic needs of its people.ABSTRAKMakalah ini mengajukan reinterpretasi karakteristik mustahiq zakát fī sabīlillāh , antara makna sempit hanya untuk tentara relawan yang ikut tempur dalam peperangan dan makna luas yang mencakup semua sisi ketaatan. Bahasan mustahiq zakát fī sabīlillāh selama ini terkonsentrasi pada luasnya makna fī sabīlillāh dalam bahasa dan spesifiknya kata fī sabīlillāh sebagai ungkapan untuk arti jihád dan peperangan. Konsep arti fī sabīlillāh yang di dalam Al-Qur`an dan hadis lebih terarah ditujukan untuk makna peperangan dirasakan tidak relevan dengan adanya nash-nash lain yang menjelaskan arti Fī sabīlillāh atau jihád untuk haji atau menuntut ilmu, serta tidak relevan pula seiring perubahan zaman dan waktu. Di sisi yang berbeda, memperluas arti Fī sabīlillāh untuk semua bentuk ketaatan juga dipandang tidak akurat dengan tujuan dan fungsi zakát yang dijelaskan oleh nash-nash wahyu. Karena itu, reinterpretasi tentang arti Fī sabīlillāh sebagai jihád sebagaimana yang dikehendaki oleh nash-nash wahyu itu sendiri dan di sisi lain oleh keputusan mayoritas ulama fiqih terdahulu, sebaiknya pengembangan arti Fī sabīlillāh dipusatkan pada arti jihád , tujuan jihád dan karakteristik khusus jihád . Dengan demikian, ditemukan dua sisi pokok konstruksi hukum zakát yang diberikan kepada mustahiq Fī sabīlillāh, yaitu perluasan makna yang didasarkan pada karakteristik dasar dari makna itu sendiri serta tujuan dan fungsi utama zakát itu sendiri yang memang berpusat pada keuangan negara dalam menata kebutuhan pokok dan dasar rakyatnya.Key Word: zakát fī sabīlillāh, mustahiq, jihad